Human consciousness as a base for sustainability in socio-economic-ecological systems. (1st January 2011) - Cuenca, Estrella Bernal; Edgar, David
Sustainability of socio-economic-ecological systems always implies a structural uncertainty coming mainly from the diversity of social values involved in the decision making processes required to manage the system. Such uncertainty cannot be reduced in any way, but needs to be managed if sustainability is to be pursued in its 'strong' meaning. This work proposes a methodology to manage structural uncertainty based upon the integration of elements from ecological economics, sociology and biology. This integration provides an approach to the strong sustainability of systems that is based on human consciousness from the perspective of the biology of knowledge and provides for a more holistic perspective for understanding and managing sustainability.